2022
DOI: 10.1002/admi.202201405
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interfaces in Ionic Liquid‐Based Hybrid Materials (Ionogels) for Sensing and Energy Applications

Abstract: Ionogels have established themselves as an intriguing type of composites, owing to their distinctive properties, including superior thermal stability, non‐flammability, tunable electrochemical stability window, and high ionic conductivity. Hybrid materials based on ionic liquids (ionogels) are held together by interfaces arising out of intermolecular interactions, including electrostatic, van der Waals, solvophobic, steric, and hydrogen bonding. The interfaces within the ionic liquid (ILs) and its multifaceted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 275 publications
(384 reference statements)
0
8
0
Order By: Relevance
“…Obviously, the concentration of ionic liquid (IL) could have a strong effect on the electrical properties and the mechanical properties as well. 22 Nevertheless, the high content of IL can be the main reason for serious liquid leakage and poor mechanical properties. In this study, the solution containing more than 30% IL failed to cure due to separation during the photocuring process.…”
Section: Properties Of Patterned Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the concentration of ionic liquid (IL) could have a strong effect on the electrical properties and the mechanical properties as well. 22 Nevertheless, the high content of IL can be the main reason for serious liquid leakage and poor mechanical properties. In this study, the solution containing more than 30% IL failed to cure due to separation during the photocuring process.…”
Section: Properties Of Patterned Devicementioning
confidence: 99%
“…In recent years, there has been a significant increase in the development of stretchable electronic sensors due to the growing demand for wearable applications. These stretchable sensors can detect and collect physical changes from the various parts of the human body, consequently modulating the mechanical stimuli into electrical signals for monitoring physiological healthcare information. Viscoelastic polymers, often conformally attached to human skin, have emerged as one of the most promising material choices for such stretchable sensors, arising from their desirable inherent characteristics of flexibility, stretchability, body friendliness, and durability, and have further led to the adoption of various novel materials and device configurations for improved aforementioned performances. However, many extensive attempts have been made to focus on and improve the stretchability and sensitivity of stretchable sensors, even exhibiting several thousand stretchability and excellent sensitivity. These attempts include multilayered composite stretchable films, nanoparticle-embedded films, microcrack or groove structures, and novel device structural architectures to improve stretchability and sensitivity. Among the stretchable materials, ionic liquid-based films have attracted much attention owing to their advantageous potential in terms of a wide range of stretchability and recovery as well as optical transparency and biocompatibility. It is well-known that these ionic liquid-containing polymer films represent an important viscoelastic electronic material in which the conducting ionic liquid molecules embedded in the insulating elastic solid polymer matrix give rise to the conductivity change due to their increased hopping distance when stretched. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, piperidinium and pyrrolidiniumbased ILs usually exhibit higher oxidation potentials than imidazolium-based ILs but lower ionic conductivity. 224,245 For instance, solid-state ionogel electrolyte prepared by confining IL [Py 13 ] + [TFSI] À and [Li] + [TFSI] À within sol-gel prepared TiO 2 gelators exhibited high electrochemical stability with the anodic limiting potential reaching about 5 V versus Li/Li + . 246 Another work done by Guo et al 206 demonstrated the ionogel membranes consisting of hydrogen-bonded supramolecular PIL-UPy copolymer networks and [DEIM] + [TFSI] À .…”
Section: Electrochemical Stabilitymentioning
confidence: 99%
“…10,11 Ionogels integrate the advantages of non-volatility, transparency, wide-range operating temperatures, high conductivity and good electrochemical stability, endowing their suitability in pressure sensors. [12][13][14][15][16][17][18][19][20] However, most existing ionogels suffer from low strength and toughness due to the high content of liquids. 21 Increasing the amount of permanent covalent crosslinking sites can readily enhance the mechanical strength but will inevitably lead to high rigidity and non-reversibility.…”
Section: Introductionmentioning
confidence: 99%